ANALISIS DAYA SAING KOPI DI DESA TLETER KECAMATAN KALORAN KABUPATEN TEMANGGUNG - Irfanda, Arif; Yuliawati, Yuliawati (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol.13, No.2, 2019, 2019)
Coffee is a plantation that grows and develops in Indonesia. In Indonesia there are many coffee-producing regions with distinctive tastes. Temanggung Regency is one of the coffee producing regions in Indonesia, but not all regions in Temanggung Regency are known as coffee producers with distinctive flavors. One of the coffee producing areas in Temanggung Regency is Tleter Village, located in Kaloran District. To find out whether coffee from Desa Tleter can be developed or not, competitiveness analysis is needed so that competitive advantage and the comparative advantage of coffee farming will be known. This study aims to determine coffee competitiveness in Tleter Village, Kaloran District, Temanggung Regency. The method used in this research is quantitative descriptive method. The sampling technique is purposive. The number of respondents in this study were 40 coffee farmers. Data retrieval is done by interviewing using a questionnaire. Competitiveness analysis is done by using the Policy Analysis Matrix (PAM). The results of the PAM analysis show the value of competitive advantage or PCR of 0, 55 and comparative advantage or DRCR of 0.55 means that coffee in Tleter Village has competitiveness.